Antioxidant Activity and Cytotoxic Potential of Parijoto (Medinilla speciosa (Reinw ex BL)) Fruit Fractions on HeLa Cell Line - Winanta, Aji; Hanik, Linta Sabila; Febriansah, Rifki (Indonesian Journal of Cancer Chemoprevention, 2021)
Parijoto (Medinilla speciosa (Reinw ex BL)) is one of the Indonesian indigenous plants widely used as traditional medicine. A previous study showed that ethanol and methanol extracts of Parijoto fruit could inhibit T47D breast cancer cells. This study explores the antioxidant and cytotoxic activities of Parijoto fruit extract and fractions on HeLa cell line. The fruits were extracted using ethanol 70% and fractionated by hexane and ethyl acetate. Furthermore, the fraction was analyzed for secondary phytochemical metabolite content using thin-layer chromatography and staining reagents. The antioxidant and cytotoxic activities were determined using the DPPH scavenging assay and the MTT assay, respectively. The ethanol extract and fraction contained flavonoid and tannin compounds. Ethanol extract, ethanol fraction, and ethyl acetate fraction of Parijoto fruit had an antioxidant activity with IC50 values of 77.3, 88.64, and 46.61 μg/mL, respectively. Ethyl acetate fraction showed the highest activity on HeLa cells with an IC50 value of 45.57 μg/mL compared to ethanol extract, ethanol fraction and n-hexane fraction with an IC50 value of 233.43, 700.75, and 534.30 μg/mL, respectively. Based on these results, the ethyl acetate fraction of Parijoto fruit had the potency to be explored further to elucidate their cytotoxicity mechanism in HeLa cells.Keywords: antioxidant activity, cytotoxicity, Medinilla speciosa, Parijoto fruit fractions.